LEAD TOXICITY AND HEALTH EFFECTS- A COMPREHENSIVE REVIEW - Mohammad Yaqoob Sarfaraz; Jailani Achak; Abdullah Haqmal (CV. Radja Publika, 2024)
Lead is a heavy metal with a low melting point and is bluish-gray, soft, thick, and malleable. It is frequently present in the environment at concentrations less than 50 mg/kg. Although Pb is often found in high amounts in nature, its presence in water is primarily attributed to human pollution and artificial activity. Pb is one of several elements, the effects of which can be harmful to human health and the environment. There are also concerns that Pb may be carcinogenic and harmful to humans. The biological half-life of Pb in the human body varies from 28 to 40 days in the blood to several years or even decades in the bone and other body tissues, and the danger associated with Pb poisoning is still unknown because of the wide range of clinical manifestations. Pb exposure has been linked to lung diseases, cardiovascular problems, neurological impact, renal impairment, reproductive toxicity, and potentially carcinogenic effects. Exposure time, diet, health status, age and general well-being can all play a role, in how individuals respond to lead poisoning. The FDA has set reference levels (IRLs) for exposure at 8.8 μg per day for women of reproductive age and 12.5 μg per day for adults. It can enter the body through either the digestive or the respiratory system. It is important to take steps to maintain a lifestyle that promotes preventive measures and enhances public health by ensuring regular monitoring of individuals who face frequent exposure to heavy metals, particularly Pb. To effectively monitor and prevent Pb exposure, it is crucial to establish comprehensive screening programs for high-risk populations and prioritize public health initiatives that focus on promoting healthy lifestyles and minimizing environmental pollution.